2022
DOI: 10.3390/biomedicines10092206
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Prospective Assessment of Genotoxic and Cytotoxic Effects of Fluoride Toothpaste and Mouthwash in Buccal Mucosal Cells

Abstract: Background: Fluorides are an essential component of oral hygiene products used to prevent dental decay. Therefore, a question arises about the potential harms of joint use of fluoridated toothpaste and mouthwashes regarding the increased amount of fluoride in the oral mucosa. Methods: This prospective, double-blinded parallel randomized clinical trial was conducted using a buccal micronucleus cytome assay (BMCyt assay). Forty-one participants were randomly assigned to the two groups. All participants used the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…It can directly inhibit enzymes like enolase involved in glycolysis leading to ATP depletion and mitochondrial dysfunction 15 . This triggers the intrinsic apoptotic pathway in mucosal epithelial cells and fibroblasts 16 . Sustained apoptosis results in the release of profibrotic factors like TGF‐beta that stimulate fibroblasts and promote collagen deposition and extracellular matrix remodelling 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can directly inhibit enzymes like enolase involved in glycolysis leading to ATP depletion and mitochondrial dysfunction 15 . This triggers the intrinsic apoptotic pathway in mucosal epithelial cells and fibroblasts 16 . Sustained apoptosis results in the release of profibrotic factors like TGF‐beta that stimulate fibroblasts and promote collagen deposition and extracellular matrix remodelling 17 …”
Section: Discussionmentioning
confidence: 99%
“…15 This triggers the intrinsic apoptotic pathway in mucosal epithelial cells and fibroblasts. 16 Sustained apoptosis results in the release of profibrotic factors like TGF-beta that stimulate fibroblasts and promote collagen deposition and extracellular matrix remodelling. 17 Fluoride-induced oxidative stress can also activate inflammatory pathways like NF-kB and increased expression of cytokines like IL-8 and COX-2.…”
Section: Statistical Analysis (Tablementioning
confidence: 99%
“…A previous in vivo study [25] showed that the concurrent use of toothpaste containing fluoride and fluoride mouthwash did not result in any cytotoxic or genotoxic effects on buccal mucosal cells. Another in vivo study further substantiated that the use of fluoridecontaining toothpastes did not induce cytotoxicity or genotoxicity in buccal epithelial cells; however, sodium lauryl sulfate (SLS)-containing toothpastes resulted in cytogenetic damage [26].…”
Section: Introductionmentioning
confidence: 90%